PERBEDAAN MOTIVASI BELAJAR MAHASISWA PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN UNIVERSITA RIAU ANGKATAN 2013 SAMPAI 2015 (DITINJAU DARI JALUR SELEKSI PBUD, SBMPTN DAN SNMPTN) - Novita Aria; Gimin Gimin; Zahirman Zahirman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to determine whether there are differences in student learning motivation of the workforce in 2013 and 2015 as well as whether there are differences in motivation to learn by force in 2013, 2014 and 2015, the pathway on selection PBUD, SBMPTN and SNMPTN on Pancasila and Citizenship Education University of Riau. Sampling in this research is proportional sampling proporsif. The population in this study were 183 students and a sample of 47 students, which is 9 PBUD students, 20 students and 18 students SBMPTN SNMPTN. Data collection techniques through observation, documentation and questionnaires, the questionnaire consists of 36 statements. Data were analyzed with descriptive quantitative. Data were analyzed by percentage. From the calculation of the percentage of respondents, obtained PBUD student learning motivation, SBMPTN and SNMPTN have a difference of 1%. Based One Way Anova statistical test with a level of 95% (a) = 0.05, obtained sig. 0.002 <0.05 conclude that Ha received or no difference in learning motivation of the students who enter the path PBUD, SBMPTN and SNMPTN Pancasila and Citizenship Education University of Riau. It can be concluded that the overall average of students' learning motivation Pancasila And Citizenship force in 2013 the average amount coming from SNMPTN (135.67), from the path of SBMPTN (134.25), from the path of PBUD (137.5), concluded that students' learning motivation the highest of the entrance of the lane PBUD (137.5). Forces in 2014 the average amount coming from SNMPTN (138), from the path of SBMPTN (132.75), and on the path PBUD (137.33), concluded that the students' learning motivation the highest of the entrance of SNMPTN (138 ). And the force in 2015 the average number of students learning motivation coming from SNMPTN (137.5), of SBMPTN track (130), from PBUD track (134), concluded that the students' learning motivation the highest of the entrance of SNMPTN ( 137.5)Keyword : Difference, Motivation, Path Selection PBUD, SBMPTN and SNMPTN